NORMA PERSATUAN SEBAGAI BATASAN PERBUATAN PIDANA PENYEBARAN UJARAN KEBENCIAN MELALUI INTERNET - Christianto, Hwian (Veritas et Justitia, 2020)
The Law no 11 of 2008 contains a penal rule against spreading hatred by the means of the internet (or digital social media). The enforcement of this penal sanction, due to its vagueness on the meaning of the term hate and spread of hate, consequently result in a public debate on how it impacts on people’s right of free expression. Apparently this vagueness opens up the possibility to limit even suppress freedom of expression. Using a juridical normative approach, this article discusses the leitmotiv of the above penal sanction.  The author suggests that the express purpose of this article is to secure the unity and integrity of a pluralistic society.